Legal Protection for Doctors in Telemedicine Services: A Human Rights and Comparative Law Perspective - Wahyudin, Bob; Arie, Marthen; Irwansyah; Suwondo, Slamet Sampurno; Assefa, Rahel (Jurnal Suara Hukum, 2025)
The practice of telemedicine is part of technological development that optimizes technology-based healthcare services, which can guarantee health rights for the community. However, the practice of telemedicine actually raises problems because there has not yet been optimal protective measures for doctors. This research aims to analyze the issues surrounding the regulation of telemedicine practices and their relation to the development of human rights in the health sector, as well as a comparative legal study of telemedicine regulations in Indonesia, Malaysia, and Ethiopia. This research is a normative legal study that emphasizes conceptual, comparative, and legislative approaches. The research results affirm that the right to health is a fundamental part of human rights that has been globally recognized since the WHO Constitution in 1946 and the Universal Declaration of Human Rights in 1948. As time progresses, the forms of fulfilling these rights also evolve, including through technology-based healthcare services such as telemedicine. Telemedicine has emerged as an important innovation in addressing the challenges of access and equity in healthcare services, particularly for communities in remote areas or with limited mobility. The findings of this study indicate that the regulation of telemedicine in Indonesia, Malaysia, and Ethiopia shares similarities in recognizing the importance of telemedicine within the national healthcare system. However, there are striking differences in regulatory approaches, infrastructure readiness, and legal protections for medical personnel. Malaysia has the most mature legal framework with the Telemedicine Act 1997 and data protection through the PDPA 2010. On the other hand, Indonesia does not yet have comprehensive specific regulations that protect doctors in telemedicine practice, while Ethiopia is still in the early stages of policy development. Therefore, there is a need for adaptive and comprehensive regulatory updates to ensure legal certainty, protection of rights, and sustainability of technology-based healthcare services in each country, particularly Indonesia.